Deoxygenative cross-electrophile coupling of benzyl chloroformates with aryl iodides. Issue 17 (5th April 2019) - Pan, Yingying; Gong, Yuxin; Song, Yanhong; Tong, Weiqi; Gong, Hegui
Abstract : We disclose herein a Ni-catalyzed benzyl C–O bond radical fragmentation/cross-electrophile coupling of benzyl chloroformates with aryl iodides to generate diaryl methane derivatives. Abstract : This work describes Ni-catalyzed cross-electrophile coupling of benzyl chloroformate derivatives with aryl iodides that generates a wide range of diaryl methane products. The mild reaction conditions merit the C–O bond radical fragmentation of benzyl chloroformates via halide abstraction or a single electron reduction by a Ni catalyst. This work offers a new substrate type for cross-electrophile couplings.